2022
DOI: 10.1111/jan.15307
|View full text |Cite
|
Sign up to set email alerts
|

Nurse manager intentional rounding and outcomes: Findings of a systematic review

Abstract: Aim To summarize the evidence available on Nurse Manager Intentional Rounding (NMIR) describing the main characteristics and methodological quality of studies available, the features of rounding and the outcomes as measured to date. Design A systematic review. Data Sources Electronic databases, including MEDLINE‐EBSCHOST, PubMed, CINAHL, Scopus, Cochrane, Clinicalkey, ScienceDirect, OVID, Sage Journals and Web of Science, were searched up to June 2021. Review Methods The Preferred Reporting Items for Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In the organizational context, using a call bell for assistance is considered a leading cause of interruption of nursing work (D'antonio et al., 2014). In this case, rounding is a nursing organizational methodology that, as shown in several previous studies, can lead to a decrease in requests for assistance as well as an increase in patient satisfaction and safety (Bayram et al., 2022; Christiansen et al., 2018; Kelley, 2017; Manderscheid, 2022).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the organizational context, using a call bell for assistance is considered a leading cause of interruption of nursing work (D'antonio et al., 2014). In this case, rounding is a nursing organizational methodology that, as shown in several previous studies, can lead to a decrease in requests for assistance as well as an increase in patient satisfaction and safety (Bayram et al., 2022; Christiansen et al., 2018; Kelley, 2017; Manderscheid, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…The patient-initiated care calls represent, from a care perspective, a lifeline for hospitalized patients (Bayram et al, 2022;Kalman, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard of effective decision-making can be fostered by ensuring nurses are present and engaged in care decisions though both interprofessional and nurse leader rounds. 16,17 In healthcare's highly demanding environments, engaging nurses in decisions about patient care, unit culture, and organizational initiatives is essential, both to the quality of those decisions and as recognition of nurses' valuable and unique perspective. A systematic review found that including nurses in decisions fostered improved patient outcomes, engagement, and professional accountability.…”
Section: True Collaboration and Effective Decision-makingmentioning
confidence: 99%
“…Ensuring that individual voices are heard within a team is crucial to successful collaboration and subsequent decisions. The standard of effective decision-making can be fostered by ensuring nurses are present and engaged in care decisions though both interprofessional and nurse leader rounds 16,17. In healthcare's highly demanding environments, engaging nurses in decisions about patient care, unit culture, and organizational initiatives is essential, both to the quality of those decisions and as recognition of nurses' valuable and unique perspective.…”
Section: True Collaboration and Effective Decision-makingmentioning
confidence: 99%